PENCEGAHAN KENAKALAN REMAJA MELALUI IR/EDUCATION - Chairiyah, Royani; RA, Mella Yuria; Gustina, Irwanti (Jurnal Abdi Insani, 2024)
Juvenile delinquency is an act / crime / offense committed by adolescents that is unlawful, anti-social, anti-moral, and violates religious norms. Juvenile delinquency occurs because it is influenced by internal factors and external factors can have an impact on the teenager himself, family, and the community. Efforts made in tackling juvenile delinquency behavior can be grouped into preventive, curative, corrective and preservative actions can be carried out in the family, school and community environment. This PKM activity aims to provide understanding to adolescents regarding the prevention of juvenile delinquency in the form of education. The implementation of this PKM was carried out at SMK Bina Mandiri Depok on January 26, 2024 in the Classroom which was attended by 64 students and class XII students. Implementation method with lectures, discussions, active participation, questions and answers, evaluation and follow-up. This activity was attended by adolescents, the majority of the female sex 64.06%, the majority of adolescents aged mid-15-17 years 92.19%. Dedication material on Introduction to Juvenile Delinquency, Negative Impact of Juvenile Delinquency, Driving Factors of Juvenile Delinquency Solution and Prevention, Family Role, Social Skills Development, Importance of Education. The evaluation results showed an increase in knowledge related to juvenile delinquency with the pre-test score result was 53.78 after the activity there was an increase in the post-test score results to 91.78. The good response of the participants was seen with enthusiasm to follow it from the beginning to the end of the activity. There is an increase in adolescent knowledge.  It is expected that adolescents increase self-awareness, provide a strong foundation, become responsible and productive individuals.